The rules on international jurisdiction in matters of parental responsibility in Council Regulation (EU) 2019/1111 of 25 June 2019 - Bernardo San José, Alicia (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper analyzes the rules of international jurisdiction on parental responsibility in the Council Regulation (EU) 2019/111 (Brussels II ter Regulation). These rules are examined with a view to identifying the amendments and improvements introduced by the European legislator to the new Regulation, as compared to the rules of the current Council Regulation (EC) nº 2201/2003 (Brussels II bis Regulation), which will be repealed from 1 August 2022. In addition, a comprehensive study is carried out on the jurisprudence of the European Court of Justice on how the jurisdiction rules must be interpreted within the meaning of BR II bis and their applicability to BR II ter.
Keywords: international jurisdiction; parental responsibility; best interests of the child; habitual residence; forum non conveniens